2017
DOI: 10.1038/s41598-017-11078-3
|View full text |Cite
|
Sign up to set email alerts
|

Formation of ferromagnetic Co–H–Co complex and spin-polarized conduction band in Co-doped ZnO

Abstract: Magnetic oxide semiconductors with wide band gaps have promising spintronic applications, especially in the case of magneto-optic devices. Co-doped ZnO (ZnCoO) has been considered for these applications, but the origin of its ferromagnetism has been controversial for several decades and no substantial progress for a practical application has been made to date. In this paper, we present direct evidence of hydrogen-mediated ferromagnetism and spin polarization in the conduction band of ZnCoO. Electron density ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 74 publications
1
19
0
Order By: Relevance
“…In particular, for Co-doped ZnO thin films it has been shown that a large enhancement in the ferromagnetic behavior can be induced by a suitable atomic hydrogen treatment, without the formation of metal Co nanophases. [8][9][10][11] In the context of DMS, the MO effect is useful to investigate the strength and the nature of the ferromagnetism as arising from spin polarized carriers magnetically coupled to magnetic ions. However, due to the presence of a finite optical absorption, the polarization of the transmitted light rotates and turns from linear (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, for Co-doped ZnO thin films it has been shown that a large enhancement in the ferromagnetic behavior can be induced by a suitable atomic hydrogen treatment, without the formation of metal Co nanophases. [8][9][10][11] In the context of DMS, the MO effect is useful to investigate the strength and the nature of the ferromagnetism as arising from spin polarized carriers magnetically coupled to magnetic ions. However, due to the presence of a finite optical absorption, the polarization of the transmitted light rotates and turns from linear (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These typically induce a larger strain due to bending at a larger angle, as shown in Figure d,e. However, the sensor responses were relatively slow upon release, which is probably attributed to the softness and viscoelastic behavior of the composite film . One may be able to improve the recovery time by further optimizing the materials used in the conductive composite.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a mass of microstructures was utilized such as micropyramidal, microdome, microcavity, microcracks, thickness‐gradient structures, even metamaterial structure . Biomaterials, nanocomposites, triboelectric and piezoelectric materials, stimuli‐responsive polymers, hydrogels, and so on, were exploited to enhance the functionalities and to extend the limits owned by traditional silicon‐based materials . Aforementioned, multiple receptors are involved in the formation of tactile sensation, which has also inspired the design and integration of artificial sensors with versatile sensing capabilities …”
Section: Understanding Sensory Memorymentioning
confidence: 99%